2020
DOI: 10.1111/anu.13156
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inorganic monophosphates in high plant ingredient‐based diets influence nutrient digestibility, postprandial macro‐mineral status and immune functions of juvenile rainbow trout,Oncorhynchus mykiss

Abstract: Inorganic monophosphates supplementation effects in high plant ingredient-based diets of juvenile Oncorhynchus mykiss were evaluated by feeding four experimental diets supplemented with 11.4, 10.0, 11.5 and 10.0 g/kg of monocalcium phosphate (MCP), monoammonium phosphate (MAP), monopotassium phosphate (MKP) and monosodium phosphate (MSP), respectively. After 60 days, MAP and MKP supplemented groups showed improved growth and feed intake (p > .05). Apparent digestibility coefficient of dry matter (ADC DM) was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Dietary P levels were met by adjusting the supplementation of inorganic P in the form of mono-ammonium phosphate (MAP) ( Table 1 ). Next to mono-sodium phosphate, MAP represents a source of inorganic phosphates with the highest mineral digestibility for salmonids leading to the lowest total P losses [ 49 , 50 , 51 ]. Commercial diets use predominantly MAP as a source of dietary P, thus it was used in this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary P levels were met by adjusting the supplementation of inorganic P in the form of mono-ammonium phosphate (MAP) ( Table 1 ). Next to mono-sodium phosphate, MAP represents a source of inorganic phosphates with the highest mineral digestibility for salmonids leading to the lowest total P losses [ 49 , 50 , 51 ]. Commercial diets use predominantly MAP as a source of dietary P, thus it was used in this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on rainbow trout [20] have stated that both MAP and MSP have higher levels of apparent P digestibility (≈90%) compared to other inorganic phosphates, such as MCP. Likewise, a recent study [21] reported an improvement in nutrient digestibility, mineral bioavailability and immune functions of MAP, monopotassium phosphate (MKP) and MSP when compared with MCP in high plant ingredient-based diets. On the other hand, from an environmental point of view, it should be considered that MAP can release a greater amount of non-protein nitrogen (N) into the water, probably as undigested ammonia through the feces released by fish [22].…”
Section: Introductionmentioning
confidence: 98%